Some prosodic aspects in Kannada - Nandini H M (Journal of All India Institute of Speech and Hearing, 2020)
Speech   is   defined   as   the   concurrent motor  functions of respiration,  phonation, resonance  and  articulation  prosody. Prosody has been viewed as decorative ornamentation, functioning to make speech more  aesthetically pleasing.   Intonation is one   aspect   of  prosody, other  aspects being stress and rhythm.